SISTEM INFORMASI OSIS BERBASIS WEB PADA SMAN 2 CIKARANG PUSAT - Hardianto; Abdul Halim Anshor; Edora (Teknik Informatika, Universitas Pelita Bangsa, 2024)
SMAN 2 Cikarang Pusat, an A-accredited high school established in 2005, has shown great achievements. However, the school's student council still faces obstacles in manual administrative management, such as document storage, member data collection, as well as information dissemination and activity registration. This leads to access difficulties, increased risk of errors, and lack of efficiency. This research proposes the implementation of an integrated web-based student council information system to overcome these problems. The system aims to improve the efficiency of document storage, member data collection, and information dissemination of student council activities. It is expected that this system can speed up the administrative process, improve data accuracy, and facilitate access to information, thus supporting a more modern and effective student council performance in the digital era. By using the Prototype development method, this system allows continuous feedback from users to produce a product that suits the needs of the organization, while strengthening better management and decision-making. This research provides a solution to the challenges faced by the student council of SMAN 2 Cikarang Pusat in managing an organization that is more adaptive to technological developments.